FOLKLORE, ROMANTICISM AND ETHNOCULTURAL FOUNDATIONS IN N.V. GOGOL’S EARLY PROSE: EVENINGS ON A FARM NEAR DIKANKA AND VIY (World Bulletin of Education and Learning, 2026)
The article examines the folklore sources, romantic foundations, and ethnocultural specificity of N.V. Gogol’s early prose, primarily the cycle Evenings on a Farm Near Dikanka and the novella Viy. It is emphasized that these works belong to the period in which the most important features of Gogol’s artistic thinking had already emerged, while his connection with romantic poetics, folklore imagery, and the ethnocultural world of Little Russia remained especially evident.
Keywords: N.V. Gogol, early prose, folklore, romanticism, ethnocultural tradition, Evenings on a Farm Near Dikanka, Viy, Little Russia, folk demonology, artistic world.